INOVASI BAHAN AJAR ARITMATIKA SOSIAL BERLANDASKAN PROBLEM SOLVING PADA KELAS VII - Suharti Suharti; Sri Nensi Roslan; Mardhiah Mardhiah; Fitriani Nur (IKIP Siliwangi, 2022)
The type of research used is Research and Development with reference to the Plomp development model which consists of several phases, namely the preliminary investigation phase, the design phase, the realization phase and the test, evaluation and evaluation phase. revision (Test, Evaluation and Revision). The product developed in the form of teaching materials, namely problem solving based modules on social arithmetic material, the test subjects in this study were class VIIB students of SMPN 19 Bulukumba with 30 students. The instruments used in this study were expert validation sheets, student activity observation sheets, teacher ability observation sheets in managing learning, student response questionnaires, teacher response questionnaires, and learning outcomes tests. Based on the results of the limited trials carried out, it was found that (1) the results of the validation of teaching materials were 4.4 in the